Elevated plasma concentrations of lipoprotein (a) are associated with cardiovascular diseases in patients with early-onset type 2 diabetes mellitus - Zhang, Juan; Sang, Jingjing; Jiang, Yanyan; Zheng, Yi; Zhang, Jing; Liu, Xuesen; Qiu, Huafeng; Zhao, Kaijian; Sun, Hongmei; Yang, Yang; Chen, Hao; Yang, Lei (Frontiers in Endocrinology, 2025)
ObjectiveTo ascertain whether vascular complications and high lipoprotein (a) [Lp(a)] concentrations are related in individuals with early-onset type 2 diabetes mellitus (T2DM).MethodsThis observational cross-sectional study included 591 individuals with early-onset T2DM who were divided into four groups based on Lp(a) values which was measured using immunoturbidimetry and presented as mg/dL: high, >50; intermediate, 30≤Lp(a)<50; low, 10≤Lp(a)<30; and very low, <10. The relationship between the risk of vascular complications and Lp(a) level was examined using a logistic regression model.ResultsThe median age of onset for individuals with early-onset T2DM (n=591) was 37 years, duration of diabetes was 12 years, and glycated hemoglobin (HbA1c) level was 8.8%. The median Lp(a) was 10.40 (4.80-21.80) mg/dL, and Lp(a) concentration did not correlate with age, sex, or glycemic control (P>0.05). Individuals in the low Lp(a) (OR=2.12, 95% CI 1.17-3.84, P<0.05), intermediate Lp(a) (OR=2.76, 95% CI 1.10-6.98, P<0.05) and high Lp(a) (OR=4.79, 95% CI 2.03-11.31, P<0.01) groups had an increased risk of coronary heart disease (CHD) compared with those in the very low Lp(a) group after adjustment. Nevertheless, among individuals with early-onset T2DM, there was no correlation between Lp(a) concentration and the risk of cerebrovascular disease (CVL) and microvascular complications (P>0.05).ConclusionsIn patients with early-onset T2DM, Lp(a) concentration was independently associated with CHD. Lp(a) testing is essential to determine who has a latent high risk of CHD among patients with early-onset T2DM.